ANALISIS FRAMING PEMBERITAAN MEDIA DARING MENGENAI ISU REVISI UNDANG-UNDANG KOMISI PEMBERANTASAN KORUPSI (Fakultas Dakwah dan Komunikasi, 2020)
The urgency of this research problem is how the online media CNN Indonesia.com and Republika.co.id frame the news on the issue of the revision of the Corruption Eradication Commission Law using the Robert N. Entman framing analysis tool. The results show CNN Indonesia.com framing the revision issue. The KPK Law is a movement to reject the government's attitude and see the KPK as the injured victim, while Republika.co.id frames this as an attempt by the Indonesian Parliament to strengthen the KPK not to weaken the KPK. CNN Indonesia.com places those who oppose the revision of the KPK Law more dominant than those who support the revision of the KPK Law. Meanwhile, Republika.co.id only places a chronological explanation regarding the attitude of the government and the DPR RI to reject the accusation that the DPR RI wants to undermine the KPK.